Evaluation of soil macrofauna in crop-pasture rotations with conventional tillage. - Stella Zerbino, María (Instituto de Ecología, A.C., 2010)
Soil-inhabiting invertebrates play an important role in soil processes. Soil fauna include organisms of diverse sizes and adaptive strategies. Macrofauna, large organisms with body width greater than 2 mm, influence soil properties, both directly and indirectly. Their communities are influenced by soil management and thus, have a great potential as bioindicators. The objective of this study was to evaluate the effect of different crop-pasture rotations on soil macrofauna. Treatments included continuous agriculture without (S1) and with (S2) fertilization, 33% crop - 66% pasture rotation (S4), 50% croppasture rotation (S5), and 66% crop - 33% pasture rotation (S7). The number of organisms collected varied with land use intensity; treatments S1 and S4 had the lowest and highest population densities for most taxa, respectively. The Co-Inertia analysis between soil properties and population density was significant. The first axis ordered land uses in relation to its intensity. Oligochaeta and Coleoptera adults were associated with S4, the system with highest organic carbon and total nitrogen contents. The evaluation of soil macrofauna together with soil properties is a useful tool to assess land use sustainability